The first record of Pyxidium tardigradum Van der Land, 1964 (Ciliophora) in Romania - Ciobanu, Daniel Adrian; Roszkowska, Milena; Moglan, Ioan; Kaczmarek, Łukasz (Zootaxa, 2015)
In three lichen samples collected from eastern part of Romania, three populations of Ramazzottius cf. oberhaeuseri (Doyère, 1840) infested by Pyxidium tardigradum Van der Land 1964 were found. In this short correspondence we present a first record of P. tardigradum in Romania and infestation rates in studied populations according to the different life stages.